Pricing Strategy and Quality Perception in Maintaining Customer Loyalty: Evidence from Telkomsel Surabaya - Siti Amilia Marpaung; Indah Respati Kusumasari (Journal of Computers and Digital Business, 2026)
This study examines Telkomsel’s pricing strategy in maintaining its market position in Surabaya amidst increasingly competitive conditions in the telecommunications industry. The research is motivated by the public perception that Telkomsel offers relatively higher prices than other providers but continues to maintain customer trust. Previous studies on pricing strategies mostly focused on sales volume, promotions, and market penetration, while research discussing how companies maintain relatively high prices through service quality and customer perception in the telecommunications industry remains limited. Therefore, this study aims to analyze Telkomsel’s pricing strategy in maintaining customer trust and competitiveness in Surabaya. This study uses a qualitative descriptive approach through interviews, observation, and documentation involving internal Telkomsel personnel in Surabaya. The results show that Telkomsel strengthens its market position through stable network quality, broad signal coverage, digital services through the MyTelkomsel application, and adjustments to internet packages and promotions according to customer needs. Customers consider not only price, but also the benefits and quality of service received. The novelty of this study lies in discussing strategies for maintaining premium prices through customer perceptions of service value in the telecommunications industry.